Identifying and Working with Beneficiaries When Rights Are Unclear : Insights for REDD+ Initiatives - Bruce, John (Program on Forests (PROFOR), Washington, DC, 2013)
Expert statements indicate that annually approximately 20 billion dollars will be needed to prevent 90 percent deforestation in tropical countries. Development practitioners are eager to see the benefits from REDD plus initiatives shared with local partners. Equally important to understanding how local partners might benefit are questions such as, who should derive benefits from REDD plus initiatives, and how to ensure these initiatives reach the affected households, individuals, communities, companies, and government units. Getting benefit-sharing rights is fundamental, as it will determine how REDD plus initiatives serve a broader development agenda and prevent them from centralizing decision making and enabling elite capture. This paper examines how to address this challenge by adopting a legal pluralism framework and discussing the potential role of legal instruments such as contracts. While the analysis focuses largely on REDD plus activities that involve land, forests, and carbon sequestration, many of the principles suggested are applicable in a broad sense to REDD plus projects dealing with energy and other matters. This paper explores the substantive legal issues and procedural options for identifying beneficiaries in such contexts and ways of working with them despite the legal uncertainty. It gives considerable attention to process, an approach reflecting the diversity of the situations on the ground. To explore these issues, the paper draws upon several relevant bodies of learning on forestry projects and programs, including the literatures on land, tree and forest tenure, legal pluralism, forest project design and implementation, the protection of indigenous peoples, and resettlement issues associated with development projects. The paper also explores how contracts or agreements could be used to work with the beneficiaries and clearly capture the different parties' rights and responsibilities. It examines experiences discussed in the literature, and reviews three good practice projects. Lessons are drawn from both those projects and earlier relevant experiences.